Griffith-Kelly-Sherman correlation inequalities for generalized Potts model - Ganikhodjaev, Nasir; Abdul Razak, Fatimah (Springer Netherlands, 2010)
Inspired by the work of D.G.Kelly and S.Sherman on general Griffiths inequalities on correlations in Ising ferromagnets, we formulate and prove Griffith–Kelly–Sherman-type inequalities for the ferromagnetic Potts model with a general number q of local states. We take as local state space for the q-state Potts model the set F c  = { − l, − l + 1, ⋯ ,l − 1,l},where l=\fracq-12l=2q−1. The important properties of F c for what follows are that |F c | = q and F c  = − F c .